2019
DOI: 10.3390/ma12050756
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Liposomes by a Lipopolymer Targeting Prostate Specific Membrane Antigen for Theranostic Delivery in Prostate Cancer

Abstract: Prostate specific membrane antigen (PSMA) is a marker for diagnosis and targeted delivery of therapeutics to advanced/metastasized prostate cancer. We report a liposome-based system for theranostic delivery to PSMA-expressing (PSMA+) LNCaP cells. A lipopolymer (P3) comprising of PSMA ligand (PSMAL), polyethylene glycol (PEG2000), and palmitate was synthesized and post-inserted into the surface of preformed liposomes. These P3-liposomes were loaded with doxorubicin and radiolabeled with 99mTc radionuclide to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 63 publications
(94 reference statements)
0
24
0
Order By: Relevance
“…With regard to cancer therapy, liposomes provide a good platform for in vivo delivery of many anti-tumor drugs, such as doxorubicin and paclitaxel, among other chemotherapeutic agents, as well as nucleic acids ( Chen et al, 2010 ; Wang X. et al, 2017 ). In the field of breast and prostate cancer ( Yari et al, 2019 ), the application of liposomes has been increasingly common ( Satsangi et al, 2015 ; Tang B. et al, 2020 ). Multiple paclitaxel liposomes have been demonstrated to have higher anti-tumor efficiency and improved bioavailability compared to free paclitaxel ( Han et al, 2020 ).…”
Section: Organic Npsmentioning
confidence: 99%
“…With regard to cancer therapy, liposomes provide a good platform for in vivo delivery of many anti-tumor drugs, such as doxorubicin and paclitaxel, among other chemotherapeutic agents, as well as nucleic acids ( Chen et al, 2010 ; Wang X. et al, 2017 ). In the field of breast and prostate cancer ( Yari et al, 2019 ), the application of liposomes has been increasingly common ( Satsangi et al, 2015 ; Tang B. et al, 2020 ). Multiple paclitaxel liposomes have been demonstrated to have higher anti-tumor efficiency and improved bioavailability compared to free paclitaxel ( Han et al, 2020 ).…”
Section: Organic Npsmentioning
confidence: 99%
“…For these reasons, lipid nanostructures are considered a versatile nano-platform in the field of nanomedicine and biotechnology [153,154]. Recently, a P3 lipopolymer (comprising of prostate-specific membrane antigen (PSMA) ligand, polyethylene glycol (PEG2000), and palmitate) was employed for the functionalization of liposomes for the targeted delivery of drugs and diagnostics to PSMA+ advanced/metastatic prostate tumors [155]. The investigation showed that doxorubicin loaded functionalized liposomes evidenced a higher toxicity to human prostate cancer LNCaP cells lines with respect to the non-targeted liposomes.…”
Section: Lipidsmentioning
confidence: 99%
“…Realizing these problems, Uster et al introduced the concept of post-insertion, as a technique where preformed liposomes were modified only at their external surface [36]. This technique has been successfully reported for many liposome-based drug and biologic delivery systems, and has now become central to liposome development in our lab [24,34,35,37,38]. In post-insertion technique, it is important to present stealth lipopolymers to the preformed liposomes in monomeric form.…”
Section: Discussionmentioning
confidence: 99%
“…The CMC of lipopolymers, namely HDAS-SHP, HDAS-PEG 2000 , and DSPE-PEG 2000 , was determined by PC1 photon-counting spectrofluorimeter analyses (ISS, Champaign, IL, USA), as described elsewhere [17,24]. Hydro-alcoholic solution (10% v/v ethanol in phosphate-buffered saline) of N -phenyl-1-naphthylamine (NPN, 1 ĀµM) was used as a fluorescent probe.…”
Section: Methodsmentioning
confidence: 99%